2019
DOI: 10.3389/fphys.2019.00868
|View full text |Cite
|
Sign up to set email alerts
|

miR-489-3p Regulates the Oxidative Stress Response in the Liver and Gill Tissues of Hybrid Yellow Catfish (Pelteobagrus fulvidraco♀ × P. vachelli♂) Under Cu2+ Exposure by Targeting Cu/Zn-SOD

Abstract: Copper/zinc superoxide dismutase (Cu/Zn-SOD) plays critical roles in protecting cells and tissues against oxidative damage. Excessive copper ions (Cu 2+ ) in water can damage the cells of aquatic organisms, leading to impaired growth and development and reduced antioxidant defenses. Many regulatory factors control the response to excess Cu 2+ . Among them, microRNAs (miRNAs) are important small RNAs that regulate the expression of their target genes and participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…The activity of CAT in the liver of C.gariepinus juveniles increased quickly after transportation (Day 0) but began to decline with longer recovery days, according to this study. This is consistent with the findings of Qiang et al (2019), who found that CAT activity in the liver of hybrid yellow catfish rose during the early stages of copper ion exposure but decreased as exposure time increased. Qiang et al (2017), Xie et al (2018), Jia et al (2011, all found similar results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The activity of CAT in the liver of C.gariepinus juveniles increased quickly after transportation (Day 0) but began to decline with longer recovery days, according to this study. This is consistent with the findings of Qiang et al (2019), who found that CAT activity in the liver of hybrid yellow catfish rose during the early stages of copper ion exposure but decreased as exposure time increased. Qiang et al (2017), Xie et al (2018), Jia et al (2011, all found similar results.…”
Section: Discussionsupporting
confidence: 92%
“…This corroborates the findings of Koner et al (2021), who found that SOD activity increased in the liver of Magur catfish exposed to Zinc-oxide nanoparticle-induced oxidative stress. Under copper ions exposure, SOD was found to increase in the liver of hybrid yellow catfish (Qiang et al, 2019). In comparison to the control group, mRNA expression of CAT activity increased significantly on day 0, reduced on day 3, and increased marginally on day 6.…”
Section: Discussionmentioning
confidence: 82%
“…In previous published literature, it has been recorded that the increased contents of oxidative stress parameters and reduced contents of antioxidant enzymes in tissues of visceral organs of treated fish are interlinked [ 66 , 72 , 73 ]. Moreover, lower contents of antioxidant enzymes in tissues (liver, gills, and kidneys) of cat fish [ 74 ], reduced glutathione in the liver of Delta smelt [ 75 ], Jundiara fish [ 76 ], and lower values of reduced glutathione and superoxide dismutase in plasma of gold fish [ 77 ] due to various toxicants have been recorded. In contrast to our results, increased contents of superoxide dismutase, peroxidase, reduced glutathione, and catalase in different species of fish including Nile tilapia [ 78 ], Catla catla [ 68 ], Anoplopoma fimbria [ 27 ], and Clarias gariepinus [ 79 ] reared in water having higher salinity have been recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Dose correction can balance Se and Cu 2+ in animal bodies. Cu 2+ is the structural center of SOD, and uptake of exogenous Cu 2+ may activate SOD activity (Qiang et al, 2019). Therefore, at 48 h of Cu 2+ stress, increased SOD and CAT activities in the 0.05 mg/kg group may reduce MDA accumulation in the hepatopancreas tissue of Chinese mitten crab.…”
Section: Increasing Se Content Promoted Antioxidant Regulation Beforementioning
confidence: 95%
“…In addition, aquaculture water is often polluted by large amounts of copper sulfate (Sroda and Cossu-Leguille, 2011), which is used for disease control and to clear algae (De Romaña et al, 2011). Although Cu 2+ is an essential nutrient for aquatic animals, excessive Cu 2+ in the aquatic environment or in the diet can negatively affect crustacean immunity, leading to tissue oxidative damage and liver necrosis that increase susceptibility to pathogens and cause disease outbreaks (Qiang et al, 2019). Nutrients have complex mutual promoting or inhibitory effects in the body, and Se has been shown to increase antioxidant defenses (Trevisan et al, 2011) and alleviate symptoms of poisoning and apoptosis caused by heavy metals in animals (Wang et al, 2013;Xu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%